(untitled) - N. Kalaivani , Dr. S. Sundaramoorthy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Mobile banking in banking plays a major roles in the ongoing situation, based on the up gradation of the technology, customers of the banks have started using the banking services through the use of mobile phones. Now-a-days mobile phones have become the basic need of every one which helps the consumers to make various kinds of events. The undertakings that are done with the help of mobile banking are online transfer of money ticket reservation, transfer of funds etc., Consumers attitude towards mobile banking service is base the expectation of the consumers like communication has to be properly informed, the transaction process has been with limited duration, need for interaction, ease to use, etc. Customer attitude has been varying frequently based on the changes in technology upgradation in banking system. Banking service of consumers has been more effective with the help of mobile phones. Mobile Banking has been efficiently used by the customers in order to save their time, money and effort.